Emotional Intelligence in Communication Students: Comparative Study under the Competency-Based Education Model - Palomino Flores, Paola (2019)
The aim of this study was to compare the levels of emotional intelligence (EI) of students based on the expected achievement level in competencies. Participants were 313 students (M = 20.20 years old, SD = 2.41; 61% women) of communication sciences from a private university in Lima (Perú) which uses the Competency Based Education Model. The EI was measured with the Wong-Law Emotional Intelligence Scale (WLEIS). The level in achievement of competencies groups students in: “lower level” (participants from the first three academic semesters, 45.7% of the total) and “higher level” (semesters four to tenth). There were found gender differences in EI, and thus comparative analyses were done separately by gender. Among men, there were no differences between groups in EI (lower level vs. higher level). By contrast, women from the lower level scored higher than women from the higher-level group in: others’ emotional appraisal, use of emotion, and EI total score. It is suggested to incorporate the EI competence within the teaching model of this academic institution, as well as to do longitudinal studies.